Coastal movements and estuarine use of sub-adult and adult leervis, lichia amia: results from long-term acoustic tracking - Mxo, Rebecca Vuyolwethu (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Information on fish movement is important not only for understanding a species' ecological importance, but also for developing appropriate conservation and management policies that are critical for food security and biodiversity preservation. This information is particularly important for species that occupy different habitats at different life history stages, and display predictable movement patterns, such as an annual spawning migration. Leervis Lichia amia is an estuary-dependent fishery species of high ecological and recreational importance in South Africa. There has been a steady decline in catch-per-unit-effort in the marine recreational fishery for this species over the past 20 years, and the most recent stock assessment classified the adult stock as collapsed. This study investigates L. amia multi-year coastal migrations and estuarine habitat use of sub-adult and adult fish tagged with long-life acoustic transmitters Seventy-eight L. amia (two juveniles, fifty-four subadults, and twenty-one adults) were tagged throughout their South African distribution and monitored between 2011 and 2020 producing a decade long dataset. Results show that regardless of the tagging region, clear migration patterns were observed, demonstrating that both sub-adult and adult L. amia migrate annually to KZN in the austral winter and predictably return to the WC and EC waters in the summer. The likelihood of partial migration was also identified, with the coexistence of migratory and resident behaviors within a single L. amia population. In addition, Overwintering behaviour was also observed with L. amia adults that remained resident throughout the year, foregoing the annual migration, phenomenon known as skipped spawning, and homing behaviour, where L. amia, particularly those tagged in the EC and WC, were recorded returning to previously occupied tagging locations and surrounding areas. The importance of estuaries to sub-adult and adult fish was also assessed and identified the importance of estuaries not only to subadults but also to adults. Estuary visits were strongly influenced by the environment which the fish was tagged in, temporal and seasonal changes, and life-history stages. The predictability of their migrations (almost to the day), the varied migratory behaviour (overwintering), returning to sites of familiarity post-migration, and long-term dependency on estuaries even as sub-adults and adults, provide motivation for increased protection of this species, including extending the network of estuarine protected areas in the country, and a closed fishing season, particularly during the annual winter migration.
Keywords: Lichia amia; Marine fishes Migration -- South Africa; Underwater acoustic telemetry; Marine fishes Behavior -- South Africa; Estuaries -- South Africa